Analysis The Influence of Price, Promotion, Distribution, Product Quality and Brand Image on Purchase Decision of Cereal Product - Siti Patimah; Muhammad Hasyim; Saipul Al Sukri; Didit Hadayanti; Hendrajaya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to analyze product quality partially affect the purchasing decision process, to analyze the price partially affect the purchasing decision process, to analyze promotions partially affect the purchasing decision process, to analyze distribution channels partially affect the purchasing decision process , to analyze brand image partially influence the cereal purchasing decision process and to analyze product quality, price, promotion, distribution channels and brand image simultaneously influence the purchasing decision process of Nestle Koko Krunch breakfast cereal. The conclusion of this study is that all exogenous variables have a positive effect on endogenous variables, both partially and simultaneously. Based on the results of the research conducted, it can be seen that product quality, price, promotion, distribution channels, and brand image simultaneously influence purchasing decisions. Thus, the higher the quality of the product offered, the price offered is competent and competitive, the better the promotion that is informed, the easier it is to obtain and the more evenly distributed the product distribution location itself and is complemented by a strong and positive brand image from potential customers, it will encourage consumers in making purchasing decisions for breakfast cereals.